Perlindungan Hak Maternitas Pekerja Perempuan di Kota Makassar: Tinjauan Hukum Islam dan Implementasi Undang-Undang Ketenagakerjaan - Nasir, Nurfainna; Irianto, Afifah; Mustafa, Zulhasari (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This study examines the appropriateness of the implementation of maternity rights for women workers in Makassar City and examines it from the perspective of Islamic law. This study is motivated by the importance of protecting women's reproductive rights and occupational health in an increasingly dynamic work environment. The research method used is field research with a phenomenological approach, where data is obtained through in-depth interviews, direct observation, and documentation of a number of companies in Makassar City. Data analysis is carried out through three stages, namely data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of maternity rights in several companies, such as PT Indomarco, PT Sumber Alfaria Trijaya, PT Pertamina, and PT Ruang Raya Indonesia, has been in accordance with the provisions of Law Number 13 of 2003 concerning Manpower, especially Article 81 paragraph (2) and Article 82 paragraph (1) which regulate menstrual leave, maternity leave, maternity leave, and miscarriage leave. From the perspective of Islamic law, maternity rights are seen as fundamental rights that are not only medical but also spiritual, with a postpartum period of three months as a recovery period that needs to be respected. This study recommends the need for more gender-responsive employment policies, especially in the provision of private facilities such as proper lactation rooms and simplification of administrative procedures in applying for menstrual leave, to ensure fair and efficient access for female workers. These findings are important as a contribution to the formulation of inclusive and equitable employment policies.